Examining the Validity of Constructs that Measure the Willingness to Share Waqf Information: An Exploratory Factor Analysis - Yusuff, Noraini; Johari, Fuadah; Ishak, Nor Syahidah; Misbah, Hanim; Harun, Siti Latipah; Hasbullah, Nurul Adilah; Ahmad Musadik, Siti Hajar Salwa; Ahmad, Azuan (2023)
Waqf is crucial in providing society with cost-free or affordable services. However, ensuring the sustainability of waqf contributions remains a key challenge. Hence, it is essential to establish a sustainable waqf ecosystem based on information sharing among stakeholders to maximise its societal benefits. This study adopts a quantitative research approach, utilising the information-sharing theory. The analysis employs the SPSS software to conduct Exploratory Factor Analysis (EFA) and assess the construct validity of variables measuring the willingness to share information. The study investigates the impact of trust, reciprocity, and commitment as independent factors on the willingness of waqf stakeholders in Malaysia to share information. A preliminary study was conducted between January and March 2023, involving 78 purposively sampled respondents who were Waqif, Mawquf Alaih, or knew about endowing waqf through the online waqf platform. This preliminary study evaluated the viability and reliability of the instruments used to represent the variables and relationships. The study intends to demonstrate the validity of factors influencing stakeholders' willingness to share information, thereby enhancing Malaysia's waqf co- 919 creation ecosystem. The findings will serve as input for developing an information-sharing framework and informing policy implications to improve the environment for waqf co-creation